2004
DOI: 10.1124/mol.104.003475
|View full text |Cite
|
Sign up to set email alerts
|

A Retinoic Acid Receptor β/γ-Selective Prodrug (tazarotene) Plus a Retinoid X Receptor Ligand Induces Extracellular Signal-Regulated Kinase Activation, Retinoblastoma Hypophosphorylation, G0Arrest, and Cell Differentiation

Abstract: Retinoic acid receptor (RAR)␤ is perceived to function as a tumor suppressor gene in various contexts where its absence is associated with tumorigenicity and its presence causes cell cycle arrest. Tazarotene is a prodrug selective for RAR␤/␥, thereby motivating interest in determining whether tazarotene might activate putative tumor suppressor activity. Using HL-60 human myeloblastic leukemia cells, a cell line that undergoes G 0 cell cycle arrest and myeloid differentiation in response to retinoic acid (RA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In more recent studies, tazarotene has been shown to have chemopreventive efficacy against anti-basal cell carcinomas [205]. In addition, tazarotene has been proposed to act as an anti-neoplastic agent, when used in conjunction with rexinoids [206].…”
Section: Retinoids In Disease and Therapymentioning
confidence: 99%
“…In more recent studies, tazarotene has been shown to have chemopreventive efficacy against anti-basal cell carcinomas [205]. In addition, tazarotene has been proposed to act as an anti-neoplastic agent, when used in conjunction with rexinoids [206].…”
Section: Retinoids In Disease and Therapymentioning
confidence: 99%
“…One important finding was the enrichment of Rb in its hypophosphorylated state in NSC3852-treated cells. Hypophosphorylated Rb is the active tumor suppressor state of Rb and is a marker of cells arrested in G 1 , cell differentiation, and cell senescence (Yen and Varvayanis, 1995;Knudsen et al, 1998;Yen et al, 2004). We also showed that NSC3852 is a redox-active compound that stimulates superoxide production and a transient rise in intracellular redox potential.…”
Section: Discussionmentioning
confidence: 87%
“…Other workers have shown at concentration ranging from 1 to 100 nM, ATRA, acting via RAR/RXR heterodimers, stimulates a slow but long‐lasting RAF‐1 driven increase in the activity of the MEK‐ERK map kinase signaling pathway in HL60 and other myeloid leukemic cell lines [Marchinkowska et al, 1997; Yen et al, 1999, 2004; Hong et al, 2001; Miranda et al, 2002; Glasow et al, 2005]. To test whether the RAF‐MEK‐ERK kinase pathway plays any role in the retinoid driven upregulation of steroid sulfatase activity, HL60 cells were pre‐incubated with the specific RAF inhibitor GW‐5074 or the MEK inhibitors U0126 and PD098059 for 2 h prior to treatment with 100 nM ATRA.…”
Section: Resultsmentioning
confidence: 99%
“…The PKC inhibitors GF 109293X, Gö 6976, HBBDE, and rottlerrin, the NF‐κB pathway inhibitors SN‐50, parthenolide, and MG‐132 were purchased from Affiniti Research products (Exeter, UK). We were guided in our choice of inhibitor combinations and incubation conditions by previous studies performed in HL60 and other myeloid cell lines, in which the pharmacological specificities of the inhibitors had been previously characterized [Bertagnolo et al, 1999, 2004; Cambien et al, 1999; El Marjou et al, 2000; Slosberg et al, 2000; Lopez‐Pedrera et al, 2001, 2004; Wang and Studzinski, 2001a,b; Lewandowski et al, 2002; Neri et al, 2002; Martelli et al, 2003, Wang et al, 2003; Yen et al, 2004; Zhao et al, 2004; Fong et al, 2005; Glasow et al, 2005; Lal et al, 2005]. In these experiments, we have, where possible, followed the ‘rules’ proposed by Davies et al [2000] for the evaluation of the effects of pharmacological inhibitors on cellular processes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation